Expenditure and Employment Data for the Criminal Justice System: CJEE Individual Units File and Estimates File, 1985 ([Verlag nicht ermittelbar], 1987)
This survey provides criminal justice expenditure and employment (CJEE) data and for all states, counties, and certain municipal governments. Specific variables include full- and part-time employees and payroll, expenditures for current operations, capital outlay and contributions to employee benefits, and intergovernmental expenditures paid to state and local governments. Sectors represented in this survey include police protection, judicial services, legal services and prosecution, public defense, and corrections, as well as other criminal justice services.